Guide me home [large type] : a novel - Sawyer, Kim Vogel (Thorndike Press, 2016)
1907. After tragedy leaves its mark on Rebekah Hardin's family she plans to help her parents and six siblings honor her beloved brother's memory and alleviate their poverty by working as a guide in the dangerous cave system. Kentucky's renowned Mammoth Cave presents profitable opportunities in for hardworking, capable men, but Rebekah is determined to do the job -- even if it means disguising herself. Under the wing of experienced guide Tolly Sanford, "Reb" begins to learn the complexities of the cave and the two are joined by an aspiring young cartographer, Devlin Bale. Can the God who designed miles of underground astonishment shape Devlin's ambitious plans and free Reb from the weight from the past?